(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate epididymal sperm parameters in Wistar rats following treatment with the herbal formula Hoa dam sinh tinh decoction. Subjects and methods: Male Wistar rats (n = 32) were subjected to reproductive dysfunction induction using sodium valproate at a dose of 500 mg/kg/day for 7 weeks and then randomly allocated into four groups (8 rats/group). Group 1 was sacrificed immediately for epididymal sperm assessment. The remaining 3 groups were observed for an additional 5 weeks: group 2 received distilled water, group 3 received the study herbal formula at a dose of 15g/kg/day, and group 4 received the formula at 45 g/kg/day. The evaluated parameters included epididymal weight, sperm concentration, motility, viability, and sperm morphology. Results: After 5 weeks of treatment, sperm concentration in groups 3 and 4 reached 91.63 ± 7.62 × 106/mL and 104.88 ± 12.91 × 10⁶/mL, respectively, significantly higher than that in group 2: 62.38 ± 13.50 × 10⁶/mL (p < 0.05). Sperm viability increased from 60.75 ± 10.67% in group 2 to 71.50 ± 7.80% (p < 0.05) and 76.38 ± 7.23% (p < 0.01) in groups 3 and 4, respectively. Similarly, sperm motility increased from 41.38 ± 6.16% to 53.50 ± 6.80% and 62.25 ± 8.48% (p < 0.01). The percentage of morphologically normal sperm also increased from 56.37 ± 6.95% in group 2 to 66.12 ± 4.08% and 69.75 ± 4.74% in groups 3 and 4, respectively (p < 0.05), accompanied by a reduction in abnormal sperm forms. The most pronounced improvements were observed in sperm concentration and motility, with more evident effects at the highest dose of 45 g/kg/day. Conclusion: The herbal formula Hoa dam sinh tinh decoction improved sperm quality in a sodium valproate-induced reproductive dysfunction model, as evidenced by increased sperm concentration, viability, motility, and the proportion of morphologically normal sperm. The most remarkable effects were observed in sperm concentration and motility, with the higher dose (45 g/kg/day) producing superior outcomes.